The impact of the Islamic finance sector and Covid-19 pandemic on Indonesian economic growth period 2004Q1-2021Q3 - Safira Aulia Cahyaningrum; Muhammad Ghafur Wibowo (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2022)
AbstractPurpose – The impact of Islamic financial sector and COVID-19 pandemic breakout on economic growth from 2004Q1 to 2021Q3 is examined in this paper.Method – A quantitative method employing Autoregressive Distributed Lag (ARDL) analysis was employed in this study.Result – The findings demonstrate that only the JII variable has a statistically meaningful impact on economic growth. Economic growth is influenced by the variables total assets, FDR, PYD, and COVID-19.Implication – This can happen if Islamic financial institutions or Indonesian stock markets are not performing well and don’t have a large enough market share. The notion of finance-led growth, which states that the financial sector can act as a stimulant for economic expansion, is supported by this research.Originality – This study's research data was gathered from reliable sources such as Islamic Banking Statistics of OJK, the Central Bureau of Statistics (BPS), and Yahoo Finance, ensuring their authenticity.Keywords: Islamic Finance, COVID-19, Economic Growth